Influência de atividades antrópicas sobre a avifauna ameaçada de extinção e suas implicações para a conservação da biodiversidade - Ana Claudia de Almeida (2023)
Human pressures such as deforestation, fire, overexploitation, pollution, and mining are highly degrading natural ecosystems and leading to biodiversity loss worldwide. Tropical regions are suffering more from human impacts compared to temperate regions due to intense climate and land-use changes. In association with them, other extinction drivers have threatened tropical biodiversity, such as hunting and invasive species. Biodiversity loss can also disrupt networks in natural ecosystems, negatively impacting the provision of ecosystem services. To understand how human pressures impact biodiversity and ecosystem services provision in tropical areas, we can use birds as study models. Tropical birds are at high risk of extinction due to the ongoing degradation of tropical regions, which also endangers many ecosystem services they provide. Therefore, in this thesis I investigated the effects of future climate and land-use changes on potential distributions of threatened birds and how endemic and threatened bird defaunation impacts the provision of ecosystem services. In Chapter 1, I used an ecological niche modeling coupled with land-use model to evaluate the responses of a vulnerable bird (Crax fasciolata) to separate and combined climate and land-use changes under historical and future scenarios in Brazil. The results showed an increase in environmental suitability for Crax fasciolata in Brazil in the future, but with variation between domains and future scenarios. While future projections indicate an increase in climatic suitability, the looming threat of habitat loss presents a substantial challenge. Particularly in the Pantanal and Cerrado domains, the habitat loss can result in a significant decline in environmental suitability, thereby elevating the risk of extinction for this species since they are more abundant in these domains. In Chapter 2, I integrated climate-based models generated using ecological niche modeling with forest cover data to evaluate current and future potential distributions of endemic and threatened Atlantic Forest birds, and I identified priority areas for restoration and conservation for these birds. The results showed that the majority of bird species are projected to experience a reduction in projected distributions in the near future. Additionally, the findings indicate that only a limited portion of priority areas for conservation lies within the extant protected areas. This situation heightens the vulnerability of these bird species to extinction. In Chapter 3, I investigated the impact of defaunation of these endemic and threatened Atlantic Forest birds on the ecological network structure and provision of ecosystem services in different scenarios. I have found that the network structure will remain stable due to functional redundancy, but medium to high rates of bird defaunation can cause substantial decreases in key ecosystem services. These findings highlight the urgent need for conservation efforts within the researched regions, particularly in domains experiencing severe degradation such as the Pantanal, and Brazil’s biodiversity hotspots: Atlantic Forest and Cerrado. I emphasize the critical necessity of expanding/creating protected areas, implementing natural vegetation restoration programs, strengthening control of deforestation, and eradicating overhunting and other threats to conserve endemic and threatened birds within Brazil and safeguard the ecosystem services they provide.